Esforço fiscal e carga tributária potencial dos Estados do Nordeste - Moreira, Aldemir Freire (1999)
In this paper, is estimated the potencial tax capacity and the fiscal effort for each kind of different taxes collected ió the states of Northeast Brazil in 1991 to 1996. By the use these concepties, we can make some comparisons about the fiscal situation of these states. It is expected that these estimates will have practical utility in the design of the fax reform announced by federal government, mainly in the sense that tax revenue division, through transference, be connected to the fiscal effort of each state. It is also argued in the paper that there is no room to incrase tax burden. Another hipothesis tested is that federal transfer brings inefficient state tax collection. The model used was a Sthocastic Production Frontier through specification of tax collection functions and the degree of technical inefficiency of each, federal and local, taxes. These items were used to estimate the stochastic frontier.